Analisis Deskriptif : Self Esteem Pengguna Instagram Ditinjau dari Profil Demografis - Merida, Sarita Candra; Yuliana, Yomima Viena; Tasya, Faidah Ana (Jurnal Ilmiah Wahana Pendidikan, 2024)
In Digital Era, The use of social media is increasing. Nowdays, an individual with positive self-esteem will present himself more often on social media. For Example, the people using Instagram. In fact, If the people receive appreciation in the form of positive comments, the individual becomes more valuable and their self-esteem increases. Therefore, Instagram users try to present themselves as well as possible to get positive feedback from other people. The purpose this research is to describe the self-esteem of Instagram users in terms of the demographic profile which includes the area of residence and gender of the respondent. After being able to describe the self-esteem variable, the implication of this research is that through Instagram, users can share useful content so that they can increase self-esteem. The method used in this research is descriptive quantitative. The results of this research show that the self-esteem of Instagram users is in the high category in both the city and district.